Unity of Muslims as a prerequisite for successful Islamic civilisation: Risale-i Nur’s approach - Akhmetova, Elmira (2015)
This paper is a study of Said Nursi’s thoughts on unity and solidarity of Muslims. As the papers observes, Nursi closely linked ineffectiveness of the contemporary Muslim world with widespread disunity among the diverse groups (nations) of the ummah, and, urged world-wide Muslims to re-establish unity in the way of re-attaining the previous glory and virtue of Islamic civilisation. It suggests that, for Nursi, unity of Muslims was the essence of Islam and the nature of a healthy society. Solely unity, harmony, accord and solidarity among its members make the society to function justly, and reinforce the ummah towards further progress; and vice versa, disunity, discord and antagonism lead to weakness, and, consequently, to the collapse of civilisations. Therefore, as the paper finds, Nursi considered the efforts of Muslims in the way of establishing unity as a religious obligation of his time. For him, the return to the true teachings of Islam was the only solution for the miserable situation prevailed in the Muslim world. The paper suggests that Nursi put an emphasis on personality transformation in the way of achieving unity and paid attention to reform the morale of Muslims through the light of the Qur’an, and to strengthen the Muslims’ self-confidence through psychological renewal. The paper also establishes that Nursi advocated not unity of Muslims alone, but the cooperation of all religious peoples of the world against the destructive forces of racism, nationalism, atheism and secularism. According to Nursi, such alliance was an important step towards global peace and reconciliation, of which all were in such need.